(untitled) (The Agriculturists, 2012)
The objective of the study was to understand and describe the household food security status of the marginal farmers in a selected storm surge prone coastal area of Bangladesh. The study also assessed the extent of livelihood vulnerability and coping strategies of the storm surge affected marginal farmers. To collect data from the 30 randomly selected respondents a pre-tested structured interview schedule was administered during 01 to 10 October 2010. The finding reveals that maximum marginal farmers were food insecured (56.67%), while 30% were moderately food secured and only 13% were food secured. Though adequate food was available in local markets those were beyond affordability. The partial food security was due to poor food utilization in marginal farmers family. The most three vulnerable options of livelihood for the marginal farmers were crop farming, fish farming and livestock farming. The respondent farmers adopted six self coping strategies and three assisted coping strategies to cope with the vulnerability and food insecurity. The self coping strategies were decreasing the number and size of daily meals, consumption of wild food, selling labour at very low rate, selling fixed and movable household assets, contracting new loan at a high interest rate and cultivation of short duration crop. On the other hand, assisted coping strategies include relief food, social network and begging. DOI: http://dx.doi.org/10.3329/agric.v10i1.11070 The Agriculturists 2012; 10(1): 98-103